Menguatnya Perkembangan Salafisme dan Dominasi Ekonomi Kelompok Bisnis Arab di Banyumas (Integralistik, 2019)
The development of electoral politics in Banyumas which led to the increasingly strong economic and political domination of Arab business groups influenced the development of Salafism especially in urban areas. This is due to the construction of sites spreading Salafism, such as foundations. Islamic boarding schools, mosques, mosques, schools and hospitals come from donations that they provide from the benefits of doing business in the fields of property construction, furniture, education and health. Banyumas as a "bull pen" gives an illustration that the majority of the population is not too attached to religious primordial ties (abangan). This background fosters the development of kejawen Islam and Christianization. The flourishing of kejawen Islam and Christianization responds to the increasingly rapid spread of Salafism. That is because the main purpose of Salafism is the purification of Islam from heresy, shirk, and khurafat which are closely related to Islam and Christianity. In addition, Banyumas as a "bull pen" shows the strong dominance of the Indonesian Democratic Party of Struggle (PDI-P). This region even had a significant impact in winning in Central Java. Therefore, this region has always been the target of winning. However, as Salafism strengthens, the effort to win this time has been challenged by a challenger. Salafism which is included in the line of challengers is trying hard to "whiten" this region. So the use of religious issues in mass mobilization efforts is inevitable. By looking at some of these cases the dynamics of the Banyumas community which has been known as Brayan Urip (living in harmony) in a way of socializing saving time bombs that can lead to conflict due to a struggle for stronger identity and unequal control of economic resources in the implementation of electoral politics in Banyumas.Perkembangan politik elektoral di Banyumas yang mengarah kepada semakin kuatnya dominasi ekonomi-politik kelompok bisnis Arab berpengaruh terhadap perkembangan Salafisme terutama di perkotaan. Hal tersebut karena pembangunan situs-situs penyebaran Salafisme, seperti yayasan. pesantren, masjid, musala, sekolah dan rumah sakit berasal dari donasi yang mereka berikan dari keuntungan menjalankan bisnis di bidang konstruksi properti, furnitur, pendidikan dan kesehatan.Banyumas sebagai â€œkandang bantengâ€ memberikan ilustrasi bahwa mayoritas penduduknya tidak terlalu terikat dengan ikatan primordial keagamaan (abangan). Latar belakang tersebut menyuburkan perkembangan Islam kejawen dan kristenisasi. Tumbuh suburnya Islam kejawen dan kristenisasi merespon penyebaran Salafisme yang semakin pesat. Hal tersebut karena tujuan utama Salafisme adalah pemurnian Islam dari bidâ€™ah, syirik, dan khurafat yang erat kaitannya dengan Islam kejawen dan kristenisasi. Selain itu, Banyumas sebagai â€œkandang bantengâ€ menunjukkan kuatnya dominasi Partai Demokrasi Indonesia Perjuangan (PDI-P). Wilayah ini bahkan memberikan dampak signifikan dalam meraih kemenangan di Jawa Tengah. Oleh karena itu, wilayah ini selalu menjadi target pemenangan. Namun, demikian seiring menguatnya Salafisme, usaha meraih kemenangan tersebut kali ini mendapatkan tantangan cukup kuat dari penantang. Salafisme yang termasuk dalam barisan penantang berusaha sekuat tenaga â€œmemutihkanâ€ wilayah ini. Sehingga penggunaan isu agama dalam upaya mobilisasi masa tidak dapat terelakkan. Dengan melihat beberapa kasus tersebut dinamika masyarakat Banyumas yang selama ini dikenal brayan urip (hidup rukun) dalam cara bergaul menyimpan bom waktu yang dapat menimbulkan konflik karena pergulatan identitas yang semakin menguat dan penguasaan terhadap sumberdaya ekonomi yang tidak merata dalam penyelenggaraan politik elektoral di Banyumas.The development of electoral politics in Banyumas which led to the increasingly strong economic and political domination of Arab business groups influenced the development of Salafism especially in urban areas. This is due to the construction of sites spreading Salafism, such as foundations. Islamic boarding schools, mosques, mosques, schools and hospitals come from donations that they provide from the benefits of doing business in the fields of property construction, furniture, education and health. Banyumas as a "bull pen" gives an illustration that the majority of the population is not too attached to religious primordial ties (abangan). This background fosters the development of kejawen Islam and Christianization. The flourishing of kejawen Islam and Christianization responds to the increasingly rapid spread of Salafism. That is because the main purpose of Salafism is the purification of Islam from heresy, shirk, and khurafat which are closely related to Islam and Christianity. In addition, Banyumas as a "bull pen" shows the strong dominance of the Indonesian Democratic Party of Struggle (PDI-P). This region even had a significant impact in winning in Central Java. Therefore, this region has always been the target of winning. However, as Salafism strengthens, the effort to win this time has been challenged by a challenger. Salafism which is included in the line of challengers is trying hard to "whiten" this region. So the use of religious issues in mass mobilization efforts is inevitable. By looking at some of these cases the dynamics of the Banyumas community which has been known as Brayan Urip (living in harmony) in a way of socializing saving time bombs that can lead to conflict due to a struggle for stronger identity and unequal control of economic resources in the implementation of electoral politics in Banyumas.